Condoms Use Behavior Among Female Sex Worker’s Clients In Semampir Of Kediri - Kristanti, Shinta (Jurnal Penelitian STIKES Kediri, 2012)
Risky sexual behavior to onset progression of HIV-AIDS, including sexual behavior. This study aimed to analyze the factors that influence the behavior of condom use on the FSW’s clients in Semampir Kediri. This study used quantitative methods to the design of explanatory research with cross sectional approach. A triangulation of qualitative data used to support the results of quantitative analysis were excavated from WPS and pimps as a cross check answers FSW’s clients, the means used was to in-depth interviews and Focus Group Discussion on the FSW and pimps. Sample size was 66 people. Univariate data analysis, with chi-square bivariate and multivariate logistic regression. Results showed most respondents (71.2%) behave consistent in using condoms.Variables related to condom use behavior in FSW were support of friends and support of FSW. Support of friend was the most influential variable on the practice of using condoms to FSW’s clients and the OR value was 56,375.